2021
DOI: 10.1161/strokeaha.119.028832
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Assessment of the Motor System in Patients With Chronic Ischemic Stroke

Abstract: Background and Purpose: Despite continuing efforts in the multimodal assessment of the motor system after stroke, conclusive findings on the complementarity of functional and structural metrics of the ipsilesional corticospinal tract integrity and the role of the contralesional hemisphere are still lacking. This research aimed to find the best combination of motor system metrics, allowing the classification of patients into 3 predefined groups of upper limb motor recovery. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
1
10
0
1
Order By: Relevance
“…Overall, Nazarova et al 11 showed that simple measures derived from diffusion MRI or TMS are insufficient for a correct outcome classification, in line with some previous reports. 3 Furthermore, their findings suggest that the combination of several CST FA measures including the Fréchet distance may provide a better proxy of upper limb motor function.…”
Section: See Related Article P 241supporting
confidence: 65%
See 3 more Smart Citations
“…Overall, Nazarova et al 11 showed that simple measures derived from diffusion MRI or TMS are insufficient for a correct outcome classification, in line with some previous reports. 3 Furthermore, their findings suggest that the combination of several CST FA measures including the Fréchet distance may provide a better proxy of upper limb motor function.…”
Section: See Related Article P 241supporting
confidence: 65%
“…Although these results need to be replicated in larger samples, especially regarding the Fréchet distance, the relevance of microstructural metrics as potential biomarkers can be paralleled with other reports suggesting that diffusion MRI measures from a set of white matter tracts could predict walk recovery. 12,13 Finally, Nazarova et al 11 showed no benefit of a functional and structural multimodal approach. This may appear counter-intuitive according to the view the more, the better, as multimodal approaches are supposed to provide complementary information.…”
Section: See Related Article P 241mentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, it has been observed that the different somatotopically adjacent muscle representations could have different excitability profiles [ 95 , 107 , 118 ]. Albeit, at the group level the effect size may be minor or acceptable, at the individual level the clinical significance for such different profiles may be crucial [ 95 , 119 , 139 , 140 , 141 ]. This means that if a muscle has a lower rMT for activation and a steeper rise for the input–output curve than the other mapped muscles, the motor map will be biased due to the responses of that muscle, and will mostly present the representation area of that specific muscle over the other mapped muscles.…”
Section: Methodological Considerations On Application Of Ntms Motor Mappingmentioning
confidence: 99%